PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DARI HASIL EKSPERIMEN PENGARUH DOSIS URIN SAPI DENGAN PENAMBAHAN REBUNG BAMBU DAN PUMAKKAL TERHADAP PERTUMBUHAN DAN PERKEMBANGAN TERONG PONDOH (Solanum melongena L.) - Dian Anggarawati; Agus Sutanto; Dasrieny Pratiwi (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2024)
This study aimed to examine the impact of different doses of cow urine with the addition of bamboo shoots and Pumakkal on the growth of Pondoh eggplant plants. The researchers also sought to determine the most effective dose among these treatments. Additionally, the study aimed to utilize the research findings as a resource for biology learning through Learner Worksheets (LKPD). The research followed an experimental design using a completely randomized design (RAL), and the data were analyzed using Anava. The results indicated that the stem height and wet weight of pondoh eggplant fruit were significantly influenced by the treatments. Further analysis using the BNJ test identified treatment 3, comprising a dose of 300 mL of cow urine with bamboo shoots and Pumakkal, as the most effective. The research outcomes were utilized to create a biology learning resource called Project Based Learning (PjBL) based LKPD. The validation of the material, language, and design by experts yielded highly favorable results. The study concluded that the mixture of cow urine with bamboo shoots and Pumakkal positively impacted the growth of cow urine.